Universal coded ultrasound imaging system with software processing - Lewandowski, Marcin; Nowicki, Andrzej (Archives of Acoustics, 2007)
Coded transmission is a technique to solve the inherent compromise between penetrationand resolution required in ultrasound imaging. Our aim was to examine the performance ofthe coded excitation in HF (20–35 MHz) ultrasound imaging. For this purpose a novel realtimeimaging system has been developed. The digital programmable coder-digitizer modulesupports arbitrary coded waveform generation and RF echoes sampling up to 200 MSPS.All digital RF and image processing was implemented in software. The system performancewas evaluated with a single thick-film transducer (focused 25 MHz, 75% bandwidth) scanninghead. The RF echoes were acquired from a perfect reflector located with 1 cm of tissuemimicking material. Single sinus burst and 16-bits Golay codes excitations were evaluated.SNR gain for the Golay codes (referenced to single burst) of 15 dB for 20 MHz and 16 dBfor 35 MHz were obtained. The axial resolution measured at half maximum was 35 ns for20 MHz and 25 ns for 35 MHz for both single burst and the Golay codes. It clearly shows thatthe Golay codes can perfectly restore the resolution while giving respectable SNR gain.